Morbidity and Mortality Conferences: A Mini Review and Illustrated Application in Veterinary Medicine - Pang, Daniel S. J.; Rousseau-Blass, Frédérik; Pang, Jessica M. (Frontiers in Veterinary Science, 2018)
This mini review presents current knowledge on the role of Morbidity and Mortality Conferences (M&MCs) as a powerful educational tool and driver to improve patient care. Although M&MCs have existed since the early 20th century, formal evaluation of their impact on education and patient care is relatively recent. Over time, M&MCs have evolved from single discipline discussions with a tendency to focus on individual errors and assign blame, to multidisciplinary, standardised presentations incorporating error analysis techniques and educational theory. Current evidence shows that M&MCs can provide a valuable educational experience and have the potential to generate measurable improvements in patient care.